2013
DOI: 10.1186/2041-2223-4-27
|View full text |Cite
|
Sign up to set email alerts
|

Metabarcoding avian diets at airports: implications for birdstrike hazard management planning

Abstract: BackgroundWildlife collisions with aircraft cost the airline industry billions of dollars per annum and represent a public safety risk. Clearly, adapting aerodrome habitats to become less attractive to hazardous wildlife will reduce the incidence of collisions. Formulating effective habitat management strategies relies on accurate species identification of high-risk species. This can be successfully achieved for all strikes either through morphology and/or DNA-based identifications. Beyond species identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Second, our study confirmed the value of using multiple markers, but suggests that previous studies based on a mix of nonoverlapping specific markers each targeting a particular dietary component (e.g., Coghlan et al, ; Groom et al, ; Robeson et al, ; Sullins et al, ) may not be sufficient to overcome marker biases and thus provide a reliable diet composition. This is because markers considered universal for a given taxonomic clade may still have considerable variations in affinity across taxa within that clade, and thus may not amplify some important items in the diet (Aizpurua et al, ; Alberdi et al, , ; Bowser et al, ; Clarke et al, ; Kaunisto et al, ; Piñol et al, ).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Second, our study confirmed the value of using multiple markers, but suggests that previous studies based on a mix of nonoverlapping specific markers each targeting a particular dietary component (e.g., Coghlan et al, ; Groom et al, ; Robeson et al, ; Sullins et al, ) may not be sufficient to overcome marker biases and thus provide a reliable diet composition. This is because markers considered universal for a given taxonomic clade may still have considerable variations in affinity across taxa within that clade, and thus may not amplify some important items in the diet (Aizpurua et al, ; Alberdi et al, , ; Bowser et al, ; Clarke et al, ; Kaunisto et al, ; Piñol et al, ).…”
Section: Discussionsupporting
confidence: 71%
“…One problem that has attracted much attention is the selection of molecular markers, because primer specificity and biases can greatly affect the results of dietary studies (Alberdi et al, ; Taberlet et al, ). In general, studies build on previous knowledge of the diet of one or more species of interest, or of ecologically similar species, to select a primer that amplifies DNA from the main food items expected to be consumed (Alberdi et al, ; Coghlan et al, ). For instance, the studies of Soininen et al () and Valentini et al () used primers amplifying a fragment of the chloroplast trn L intron to analyse the diet of a number of herbivore species.…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of potentially contaminating human DNA was reduced by the addition of blocker oligos during PCR. Although these primers have been successfully used in other dietary DNA studies [6][7][8] , we detected mammalian amplicons in only four (8%) of the vulture hindgut samples (all turkey vultures). In contrast, mammalian DNA was readily amplified from most facial swabs (B90%), representing nine mammalian families (Bovidae, Canidae, Cervidae, Didelphidae, Equidae, Leporidae, Mephitidae, Procyonidae, Suidae).…”
Section: Resultsmentioning
confidence: 94%
“…(c) Relative numbers of species from different habitats, whose diet was assessed through barcoding techniques. Some species were studied more than once, in a total of 261 different wild species, two unidentified (pipit, Coghlan et al, ; and Bison sp., Willerslev et al, ), seven domesticated taxa, two studies focused on humans, and one taxa described only by a superior taxonomic rank (i.e., Muridade; Shirako et al, )…”
Section: Different Methodologies For the Assessment Of Trophic Interamentioning
confidence: 99%